Risk factors associated with contact lens related microbial keratitis - Ismail, Lili Asma; Gyanchand Rampal, Lekhraj Rampal; Abdul Rahman, Hejar; Omar, Nazri; Midi, Habshah; Ariffin, Azrin Esmady (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2016)
Introduction: Microbial keratitis is one of the most challenging complications of contact lens (CL) wear. Proper CL practice plays an important role to reduce the risk for contact lens related microbial keratitis (CLRMK). Methods: This multi-centre case-control study was conducted from January 2008 until June 2009 to determine the risk factors associated with CLRMK. Cases were defined as respondents who were treated for CLRMK, whilst controls were respondents who were contact lens wearers without microbial keratitis. Ninety four cases were compared to 94 controls to determine the risk factors for CLRMK. Results: The predictors for CLRMK were: Not washing hands with soap before handling CL (aOR 2.979, CI 1.020, 8.701 p=0.046), not performing rubbing technique whilst cleaning the CL (aOR 3.006, CI 1.198, 7.538 p=0.019) and, not cleaning the lens case with multipurpose solution daily (aOR 3.242 CI 1.463, 7.186 p=0.004). Sleeping overnight with the CL in the eye (aOR 2.864, CI 0.978, 8.386 p=0.049) and overall non-compliance with lens care procedures (aOR 2.590, CI 1.003, 6.689 p=0.049) contributed significantly to CLRMK. Conclusion: Health education and promotion in contact lens care are important and should be conducted by eye care practitioners to reduce the occurrence of CLRMK.